PENGARUH REBUSAN DAUN SIRIH MERAH (Piper crotatum) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS - Yodong ,; Tri Wiyatini; Lanny Sunarjo (Jurnal Kesehatan Gigi, 2014)
ABSTRACT Since a hundreds of years ago Red Betel Leaf (Piper crotatum) has been known in Indonesia as traditional medicine. Red betel Leaf contains chemical agents as such as flavonoid, polevenoland, karvakro that has antibacterial, antioxidant, antiseptic, and anti inflamatory, and essential oil that can reduce pain in the periodontal tissues. Purpose of the study is to the termine the inhibition effect of red betel leaf against  Staphylococcus aureus growth.   This study using quasi experiment because had no control group or comparison group. Design of study is with a random sample which boil the number of Red Betel Leaf and devide into there concentration  of 20%, 25% and 30%.Study result of the  showed that there is an influence of the concentration of red betel leaf as staphylococcus aureus growth resistor. Red betel leaf decoction has and influence on the concentration  of the staphylococcus aureus with 20%, of the  average total inhibition of 10.3mm, a concentration of  25% of the  average total inhibition of 12.5mm. Red betel leaf concentration  of 30% is the concentration  of the most  inflential in inhibiting staphylococcus aureus, as it shows the avarage total bacterial inhibition that most other  concentration. Key words : Red Betel Leaf (Piper crotatum), Staphylococcus aureus